ANALISIS PENERAPAN METODE DISKUSI MENINGKATKAN BERPIKIR KRITIS SISWA MATA PELAJARAN PPKN KELAS X - Wahyuni, Wahyuni; Mashudi, Mashudi; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractA thesis is entitled this research covers learning process using discussion method and thinking critically in learning civics after using the method. The method used in this research is descriptive research on the form of survey. The subject of this research was 10th grade students of SMA Mujahidin Pontianak. Data collection obtained in this research were interview and observation. Based on the result of data analysis concluded: 1. Learnig data obtained from interview and direct observation. 2. Summarizing data by constructing abstract. 3. Arranging data in parts. 4. Rechecking reliability of data. 5. Analyzing data by proceeding data to theory of subtantive. It is concluded that the use of discussion menthod improved studen?s critical thingking on Civics of 10th Grade of Sosial Scince in SMA Mujahidin Pontianak. Keywords: Critical thingkin, Discussion, Learning Civics